2010
DOI: 10.1007/s00104-010-1961-z
|View full text |Cite
|
Sign up to set email alerts
|

Perforationsrisiko und Patientenalter

Abstract: First episodes of SD were more frequent in younger patients (≤40) and did not involve a higher risk of perforation. The indication for treatment of acute SD should not be based on age but on the severity of inflammation and the individual situation of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Although elective resection is often recommended after single episodes of complicated acute diverticulits that were resolved with conservative treatment, such an invasive procedure following a favorable response to noninvasive methods has serious implications and should be made on an individual basis [52-55]. …”
Section: Introductionmentioning
confidence: 99%
“…Although elective resection is often recommended after single episodes of complicated acute diverticulits that were resolved with conservative treatment, such an invasive procedure following a favorable response to noninvasive methods has serious implications and should be made on an individual basis [52-55]. …”
Section: Introductionmentioning
confidence: 99%
“…The third study reported a slightly increased odds ratio (OR) for every 10-year increase of age (adjusted OR 1.16; 95% CI 1.01-1.33) [38]. The fourth study found comparable risks for both groups (adjusted OR 1.01; 95% CI 0.65-1.57) [28].…”
Section: Severity Of Diverticulitis At Presentationmentioning
confidence: 95%
“…Whereas most studies applied no explicit in-or exclusion criteria, five studies [16][17][18][19][20] that mainly focussed on the risk of recurrent diverticulitis only included a subgroup of patients such as only uncomplicated diverticulitis or only patients without colonic resection in the initial diverticulitis episode. The stage of acute diverticulitis at presentation was reported by 21 studies , rates of emergency surgery during the initial episode by 11 studies [18,24,[27][28][29]32,34,37,39,41,42], rates of percutaneous abscess drainage during the initial episode by two studies [29,32] and rates of recurrent diverticulitis by 12 studies [16][17][18][19][20]24,25,27,33,34,36,41].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirmation is essential to prevent that patients suffering from different diseases but with comparable symptoms, such as inflammatory bowel disease or irritable bowel syndrome, enter the study group. Studies that only include computed tomography-proven acute diverticulitis patients have found comparable proportions of complicated diverticulitis at presentation and comparable rates of emergency surgery in young (using cut-offs at 40 or 50 years) and elderly patients [ 17 20 ]. Nevertheless, these CT-based studies have found slightly higher rates of recurrent diverticulitis.…”
Section: Patient Subgroupsmentioning
confidence: 99%